SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

Littoral and benthic macroinvertebrate community responses to contrasting stressors in a large New Zealand river - Kevin J Collier; Mark P Hamer; Stephen C Moore (New Zealand Journal of Marine and Freshwater Research, 2014)
Large rivers present major challenges for biomonitoring and the development of biocriteria because of difficulties obtaining samples representative of the range of habitats present and a paucity of information on taxa responses to environmental conditions. We sampled littoral and deepwater benthic habitats to investigate macroinvertebrate community composition associated with organic, sediment and heated water discharges at 22 transects along a 73 km section of the lower Waikato River, North Island, New Zealand. Significant community differences in near‐field exposure versus no exposure sites were found only in littoral habitats, partly reflecting changes in relative abundances of Crustacea and Oligochaeta. Littoral and benthic habitats supported different macroinvertebrate communities, particularly downstream of the sediment input and following the onset of a river‐floodplain morphology which may have enhanced deposition of suspended sediment. Distance down river was a significant covariate for most metrics derived from benthic samples, but did not influence the relative abundance of most macroinvertebrate groups in littoral samples. Collectively, these results suggest that littoral habitats are likely to be more suitable than benthic habitats for biomonitoring since macroinvertebrate faunas were responsive to near‐field stressor exposure and were less likely to be influenced by longitudinal changes in river conditions.

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

Improved simulation of Australian climate and ENSO‐related rainfall variability in a global climate model with an interactive aerosol treatment - Leon D. Rotstayn; Mark A. Collier; Martin R. Dix; Yan Feng; Hal B. Gordon; Siobhan P. O'Farrell; Ian N. Smith; Jozef Syktus (International Journal of Climatology, 2010)
We assess the simulation of Australian mean climate and rainfall variability in a new version of the CSIRO coupled ocean–atmosphere global climate model (GCM). The new version, called Mark 3.6 (Mk3.6), differs from its recent predecessors (Mk3.0 and Mk3.5) by inclusion of an interactive aerosol scheme, which treats sulfate, dust, sea salt and carbonaceous aerosol. Other changes include an updated radiation scheme and a modified boundary‐layer treatment. Comparison of the mean summer and winter climate simulations in Mk3.6 with those in Mk3.0 and Mk3.5 shows several improvements in the new version, especially regarding winter rainfall and sea‐level pressure. The improved simulation of Australian mean seasonal climate is confirmed by calculation of a non‐dimensional skill score (the ‘ M ‐statistic’), using data from all four seasons. However, the most dramatic improvement occurs in the model's simulation of the leading modes of annual rainfall variability, which we assess using empirical orthogonal teleconnections (EOTs). Compared to its predecessors and several international GCMs, Mk3.6 is best able to capture the spatial pattern of the leading rainfall mode, which represents variability due to the El Niño Southern Oscillation (ENSO). Mk3.6 is also best able to capture the spatial pattern of the second rainfall mode, which corresponds to increased rainfall in the northwest, and decreased rainfall over eastern Australia. We propose a possible mechanism for the improved simulation of rainfall variability in terms of the role of interactive dust in Mk3.6. By further suppressing convection over eastern Australia during El Niño events, dust feedbacks may enhance rainfall variability there, in tune with the model's ENSO cycle. This suggests that an interactive aerosol treatment may be important in a GCM used for the study of Australian climate change and variability. Mechanistic sensitivity studies are needed to further evaluate this hypothesis. Copyright © 2009 Royal Meteorological Society

Mussel spat ropes provide passage for banded kokopu ( Galaxias fasciatus ) in laboratory trials - Bruno O. David; Mark P. Hamer; Kevin J. Collier (New Zealand Journal of Marine and Freshwater Research, 2009)
The use of mussel spat ropes to enable the passage of banded kokopu ( Galaxias fasciatus ) past perched culverts was tested under laboratory conditions. A 0.5 m high simulated perched culvert was fitted with one of two UV stabilised polypropylene rope types: “Russet Loop” and “Super Xmas Tree”. Four randomised replicate trials using each rope type were conducted to test their respective abilities to provide passage for “fresh‐run” banded kokopu whitebait (migrating post‐larval juveniles). There was no statistical difference in performance between the two rope types, with both performing equally well over each 3 h trial. A high proportion of fish used the ropes to successfully negotiate the structure (mean >85% individuals per trial irrespective of rope type). The high rate of successful passage over a short time period suggests that these ropes may be an effective, affordable and potentially easy retrofit to perched culverts, particularly for native species with similar climbing capabilities to banded kokopu.